Digital Transformation in Indonesian Halal Industrial Zones - Suganda, Asep Dadan; Euis Amalia; Muhammad Maksum; Nur Rohim (Universitas Pembangunan Nasional Veteran Jakarta, 2025)
Digital transformation has become a strategic imperative for enhancing the competitiveness of Indonesia’s halal industrial zones in an increasingly dynamic and transparency-driven global market. This study investigates the application of digital technologies—namely Blockchain, the Internet of Things (IoT), and Artificial Intelligence (AI)—within halal industrial areas, while identifying key challenges, emerging opportunities, and strategic development pathways. Adopting a qualitative exploratory approach, the research involved semi-structured interviews with five key informants, including industrial zone managers, officials from the Halal Product Assurance Agency (BPJPH), and representatives of halal-oriented small and medium enterprises (SMEs). Additional data were collected through on-site participant observation and document analysis of relevant policies and technical reports. Thematic analysis was employed to examine the qualitative data, followed by interpretation through a SWOT framework, which was subsequently integrated into a TOWS matrix to formulate strategic recommendations. The findings highlight three primary challenges: digital inequality among industrial zones, resistance to technology adoption, and inadequate infrastructure. These issues underscore the urgent need for regulatory harmonization by the government, increased investment in infrastructure and digital literacy by industry stakeholders, and enhanced academic engagement in Shariah-compliant digitalization research. The study proposes several actionable recommendations, including the establishment of public–private partnerships (PPPs), the implementation of certified digital training programs for halal SMEs, the creation of halal technology incubators, and the development of national standards for halal-related digital technologies. Overall, this research contributes to the discourse on building a digitally integrated, transparent, and sustainable halal industrial ecosystem in Indonesia.